2008
DOI: 10.1002/aic.11509
|View full text |Cite
|
Sign up to set email alerts
|

Steam bubble cavitation

Abstract: in Wiley InterScience (www.interscience.wiley.com).Generating hydrodynamic/ acoustic cavitation (Gogate et al.) for a useful purpose encompasses the following energy transformation steps: (1) Burning fuel in boiler. (2) Expanding the steam in a turbine generator. (3) Using electrical output from the generator to: (a) Pump water through a mechanical constriction (hydrodynamic cavitation), or (b) Operate ultrasonic transducer (acoustic cavitation). The combined loss, which is the mathematical product of each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…1) and model of Tomita-Shima (for bubble wall Mach no. Mahulkar et al 21 have investigated cavitation induced by injection of steam jet in subcooled water using numerical model for hydrodynamic cavitation. Chatterjee 18 has reported experimental and numerical studies in controlling hydrodynamic cavitation in the shear layer downstream of a sudden expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and model of Tomita-Shima (for bubble wall Mach no. Mahulkar et al 21 have investigated cavitation induced by injection of steam jet in subcooled water using numerical model for hydrodynamic cavitation. Chatterjee 18 has reported experimental and numerical studies in controlling hydrodynamic cavitation in the shear layer downstream of a sudden expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al 20 have modeled the reactiondiffusion kinetics of a cavitation bubble in flow downstream of an orifice. Mahulkar et al 21 have investigated cavitation induced by injection of steam jet in subcooled water using numerical model for hydrodynamic cavitation. For greater details on literature on hydrodynamic cavitation, we refer to the reader to state-of-the-art reviews by Gogate 22,23 and Gogate and Pandit.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the energy efficiencies for the processes based on the introduction of steam can be much higher as compared to the generation of hydrodynamic cavitation using alterations in the flow and pressure in a fluid ). Mahulkar et al (2008) have shown that direct injection of steam into sub-cooled water can be effectively used to produce cavitation with much higher energy efficiencies as compared to conventional technique of generation of hydrodynamic cavitation. It has also been reported that cavitation produced by this technique was experimentally and numerically shown to produce collapse conditions similar to hydrodynamic cavitation.…”
Section: Food Sterilizationmentioning
confidence: 99%
“…A recent study shows that if a steam bubble is introduced in a cold water pool, due to a fast condensation of the steam from the surface of this bubble a phenomena similar to the cavitational collapse of the bubble occurs. The steam bubble cavitation process was more efficient compared to conventional processes because of the elimination intermediate energyinterchange process [11]. The crystal formation due to cavitation has been attributed to a number of factors such as, 1) local temperature increase, 2) pressure changes leading to rapid cooling rates (10 7 -10 10 k•s -1 ), 3) concomitant shockwaves, which will overcome energy barriers to nucleation and promote crystal nucleation and its growth even at a modest super saturation level [12].…”
Section: Vaporous Cavitationmentioning
confidence: 99%